Interruzione del trattamento nei pazienti con schizofrenia che ricevono olanzapina o aripiprazolo: metanalisi degli studi clinici controllati - Santarlasci, Benedetta; Biricolti, Giovanni; Orsi, Cecilia (Farmeconomia. Health Economics and Therapeutic Pathways, 2005)
BACKGROUND: In schizophrenia the drop-out rate can be used as proxy of effectiveness. The drop-out evaluation is also important considering the relevant economic impact for NHS of an antipsychotic therapy discontinuation in terms of patient hospitalization and other related healthcare resources consumption. OBJECTIVE: To analyze the differences in the rates of drop-out from clinical trials between olanzapine and aripiprazole. METHODS: Literature search was based on MEDLINE, on Iowa-IDIS and Drugdex databases (1966-Dec 2004). Analysis included 12 randomized controlled trials (3.778 patients), 8 for olanzapine (2.559 patients) and 4 for aripiprazole (1.219 patients). RCT inclusion criteria were: a) Patients affected by schizophrenia; b) Randomized assignment to olanzapine or aripiprazole treatment group; c) Number of patients included in the treatment group higher than 100; d) Drop-out frequency evaluation between 4th and 26th weeks of follow-up. RESULTS: The rate of treatment discontinuation was greater for aripiprazole than for olanzapine (42,2% vs. 31,6% respectively). The comparison between drop-out percentages is statistically significant (p